2020
DOI: 10.1039/d0ob01273d
|View full text |Cite
|
Sign up to set email alerts
|

Ag(i)-Mediated hydrogen isotope exchange of mono-fluorinated (hetero)arenes

Abstract: An efficient approach to install deuterium into mono-fluorinated (hetero)arenes by Ag2CO3/Sphos mediated HIE protocol with D2O as deuterium source has been disclosed. This method showed specific site-selectivity of deuteration at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Simple silver salts have been shown to effect H/D exchange in pentafluorobenzene (or heptafluorotoluene) with D 2 O + AgOPiv (Piv = pivalate). H/D exchange with D 2 O in the position ortho to the fluorine of a fluoroarene (or a metal complex of fluoroarene) was also reported, employing Ag 2 CO 3 (or Ag 2 O) and a bulky phosphine (Scheme , eq ). Similar studies including DFT calculations have been reported with AgOC­(O)­Ad + PPh 3 (Ad = adamantyl) …”
Section: Introductionsupporting
confidence: 66%
“…Simple silver salts have been shown to effect H/D exchange in pentafluorobenzene (or heptafluorotoluene) with D 2 O + AgOPiv (Piv = pivalate). H/D exchange with D 2 O in the position ortho to the fluorine of a fluoroarene (or a metal complex of fluoroarene) was also reported, employing Ag 2 CO 3 (or Ag 2 O) and a bulky phosphine (Scheme , eq ). Similar studies including DFT calculations have been reported with AgOC­(O)­Ad + PPh 3 (Ad = adamantyl) …”
Section: Introductionsupporting
confidence: 66%
“…While the above-described silver and acid/base-catalyzed deuteration methodologies label electron-rich positions preferentially, a silver/phosphine ligand-catalyzed system similar to the one described above was recently applied to the ortho -selective deuteration of mono fluoroarenes by the same group (Scheme a). , Here, the selectivity for the ortho position presumably stems from its higher acidity, thus being in line with electronically controlled activation. Remarkably, the presence of pyridine directing groups does not affect the outcome of the silver-catalyzed reaction, rendering this methodology complementary to directed HIE.…”
Section: Hydrogen Isotope Exchangementioning
confidence: 99%
“…In the frequent situation that the base is silver carbonate or another silver salt, this mechanistic hypothesis has been unraveling. Several publications, notably from the Sanford, Hartwig, and Larrosa groups, have recently demonstrated that silver­(I) complexes are active in C–H activation even in the absence of palladium. Evidence comes from the detection of silver aryl complexes, H/D exchange reactions, and study of the kinetics of cross-coupling; a scheme summarizing the evidence may be found in ref . The evidence for silver participation has also been reviewed. We recently reported that the reaction of Ag 2 CO 3 with XPhos in the presence of pentafluorobenzene yields Ag­(C 6 F 5 )­(XPhos) and showed that this is a mononuclear complex that is linear at silver.…”
Section: Introductionmentioning
confidence: 99%